Estimating the extent of unreported crime: Results of the Second National Victimisation Survey in the light of new challenges: Estimating the extent of unreported crime: Results of the Second National Victimisation Survey in the light of new challenges (Archives of Criminology, 2025)
Victimisation surveys are an integral part of crime analysis. They complement the reality presented in official statistics, and they draw attention to victims who do not files reports with the relevant law enforcement agencies. In this article, we describe the problems in estimating undisclosed crime using the example of selected groups which are particularly invisible in terms of victimisation data collection (invisible victims): children, foreigners, prisoners and victims of cybercrime. We then present the results of the Second National Victimisation Survey, commissioned by the Institute of Justice in 2024. We compare the results with previous victimisation surveys in Poland. One of the major findings is that Poles are increasingly becoming victims of crimes committed with new technologies: theft from a bank account or payment card and online shopping fraud.